PHYTOTHERAPY FOR INFLAMMATORY DISEASES OF THE PROSTATE - N. G. Kulchenko; E. V. Yatsenko (Исследования и практика в медицине, 2019)
The article discusses the effectiveness of herbal medicine in inflammatory diseases of the prostate. This literature review presents clinical studies of the successful use of herbal ingredients in the treatment of chronic prostatitis and relief of lower urinary tract symptoms (LUTS). Biological active substances of Urtica dioica, Cucurbita moschata, Saw palmetto (Serenoa repens), and zinc are effective in the treatment of chronic prostatitis due to anti-inflammatory, antiproliferative, antiandrogenic and antioxidant action. Phytopreparations containing these substances can be recommended as the first line of correction of LUTS in chronic forgive categories III and IV; as a general tonic for men leading a sedentary lifestyle over the age of 35 years.